PENGEMBANGAN MEDIA INTERAKTIF BERBASIS SMART APPS CREATOR (SAC) PADA MATA PELAJARAN IPAS KELAS IV SD - Tri Yowanda Sari; Ida Suryani; Jayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Based on the problem at SD Negeri 23 Palembang, there has been no use of interactive media based on Smart Apps Creator (SAC) and learning is still monotonous because it still uses media that is only pasted which results in less interesting learning so that students feel bored. This research aims to produce interactive media products based on Smart Apps Creator (SAC) in science subjects in grade IV elementary school that are valid and practical. The type of research used is Research and Development (R&D) using the ADDIE model. This development resulted in a product in the form of an application that can be installed through android. The results of the interactive media research based on Smart Apps Creator (SAC) there are 3 validation experts, a) media experts obtained a score of 94.6% with the description "Very Valid", b) material experts obtained a score of 94% with the description "Very Valid", c) linguists obtained a score of 91.6% with the description "Very Valid", and the total of the total validation by experts obtained a score of 93.4% with the description "Very Valid". And there are 2 stages of trial on students, at the small group trial stage there are 8 students and 17 students at the ui stage of the large group trial, a) the small group trial obtained a score of 89.75% with the description "Very Practical", b) the large group trial obtained a score of 96.35% with the description "Very Practical", and the total of the entire trial obtained a score of 93.05% with the description "Very Practical". So it can be concluded that Smart Apps Creator (SAC) Interactive Media in the Science and Technology Subject Class IV Elementary School is declared very valid and practical.   Keywords: development,  IPAS learning, smart apps creator